Implementasi Blended Learning Dalam Pendidikan Islam - Nur Aisyah Asai; Fazil Nor, Sulfikar; Nirma Asmiranti (Indonesian Journal of Islamic Educational Review, 2024)
Blended learning is a term derived from English, consisting of two words: blended (combination) and learning. Blended learning essentially combines the advantages of face-to-face learning and virtual learning. It is a formal education program where students learn at least partly through online learning, with some degree of student control over time, place, path, and/or pace. Islamic education aims to systematically help students develop through the actualization of their potential based on the moral principles of the Qur'an, knowledge, and life skills. Despite efforts to reform Islamic education, several problems persist. Since Islam is a universal religion teaching various life aspects, sourced from the Qur'an, Sunnah, and ijtihad, it aims to ensure worldly welfare and eternal happiness while strengthening faith and piety. Islamic education is crucial for enhancing one's faith in Allah SWT. Without understanding the basics of Islamic education, individuals may find it challenging to draw closer to Allah SWT.